An assessment of users’ cyber security risk tolerance in reward-based exchange - ZHAN, Xinhui (Institutional Knowledge at Singapore Management University, 2018)
This study examines users’ risk-taking behavior in software downloads. We are interested in quantifying the degree of risks that users are willing to take in the cyber security context. We propose conducting an experiment using Amazon’s Mechanical Turk to assess the degree of risks that people are willing to take for monetary gains when they download software from uncertified sources.